Pengembangan Lembar Peserta Didik (LKPD) Interaktif Berbasis Liveworksheet Guna Meningkatkan Motivasi Belajar Peserta Didik pada Pembelajaran Blended - Novianti, Ratna Kurnia; Artharina, Filia Prima; Subekti, Ervina Eka (Indonesian Research Journal on Education, 2023)
This research is motivated by the results of observations and structured interviews with educators regarding the unavailability of special worksheets for blended learning that affect students' learning motivation during blended learning activities. The problems in the research are 1) What are the characteristics of Liveworksheet-based interactive E-LKPD to increase students' learning motivation, and 2) How is the acceptability of Liveworksheet-based interactive E-LKPD for learning activities? 3) How is the effectiveness of interactive LKPD in an effort to increase students' learning motivation? The purpose of this study was to determine the characteristics of the product and to determine the acceptability of the product used in learning activities and to determine the acceptability of interactive LKPD in learning activities and the effect of LKPD on learning motivation experienced by students. This Research and Development (R&D) research uses 5 stages of development, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The research was conducted in class IV A of SDN Manyaran 01 which involved 27 fourth grade students. Participants' responses to LKPD obtained a percentage of 90.2%, while theteacher's response was 90% with the "very feasible" criteria. The assessment of learning motivation experienced by students reached a percentage of 93.1% with the criteria of "very good", while the assessment related to learning motivation given by educators reached 93.3% with the criteria of "very good".